Novel Results and Concepts Emerging From Lipid Cell Biology Relevant to Degenerative Brain Aging and Disease - Isacson, Ole; Brekk, Oeystein R.; Hallett, Penelope J. (Frontiers in Neurology, 2019)
While very rare familial forms of proteinopathy can cause Parkinson’s disease (PD), Lewy body dementia (LBD) and age-related dementias, in-depth studies of lipid disturbances in the majority of the common forms of these diseases instead suggest a primary pathogenesis in lipid pathways. This review synthesizes a perspective from new data that point to an interdependence of lipids and proteinopathy. This article describes disturbed relationships in lipid homeostasis that causes neuropathology to develop over time and with age, which includes altered mechanisms of glia-neuron exchange of lipids and inflammatory signals.